2017
DOI: 10.3857/roj.2017.00416
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion as a negative prognostic factor for triple-negative breast cancer after surgery

Abstract: PurposeThis study aimed to evaluate the prognostic effects of lymphovascular invasion (LVI) in triple-negative breast cancer (TNBC) patients who underwent surgical resection.Materials and MethodsA total of 63 non-metastatic TNBC patients who underwent surgical resection were retrospectively investigated from 2007 to 2016 in Inje University Busan Paik Hospital. Pathological tests revealed that 12 patients (19.0%) had LVI. Approximately 61.9% (n = 39) of the patients’ samples stained positive for p53. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…However, in the high-risk subgroup with LVI and HG 3, which were identified as independent factors associated with poor DFS, the BCS+RT group showed significantly better RFFS than the MRM-alone group. This implied that there might be a role of adjuvant RT in reducing regional recurrence for patients with LVI and HG 3, which are well-known risk factors related to poor locoregional control and LN metastasis [20,26-28]. Therefore, PMRT is a consideration for patients with LVI and HG III even in the modern chemotherapy era.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the high-risk subgroup with LVI and HG 3, which were identified as independent factors associated with poor DFS, the BCS+RT group showed significantly better RFFS than the MRM-alone group. This implied that there might be a role of adjuvant RT in reducing regional recurrence for patients with LVI and HG 3, which are well-known risk factors related to poor locoregional control and LN metastasis [20,26-28]. Therefore, PMRT is a consideration for patients with LVI and HG III even in the modern chemotherapy era.…”
Section: Discussionmentioning
confidence: 99%
“…While breast conservation therapy has been established as the appropriate local therapy for most of early stage breast cancer [ 15 , 16 ], mastectomy is still performed in a significant number of patients. Moreover, considering a higher rate of locoregional recurrence in TNBC, the optimal local therapy for these patients has been under debate [ 2 - 5 ]. Regarding this issue, a meta-analysis by Wang et al demonstrated that BCS+RT was less likely to develop locoregional recurrence compared with mastectomy, but comparisons according to specific stage were not performed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC) has the higher risk for locoregional recurrence than any other molecular subtypes in the absence of effective targeted agents which are known to further decrease locoregional recurrence [ 1 ]. Therefore, there have been concerns on the potentially increased risk of locoregional recurrence after breast conservation therapy in TNBC [ 2 - 5 ]. Although a meta-analysis demonstrated the improved locoregional control by breast conserving surgery (BCS) plus radiotherapy (RT) compared with mastectomy alone in TNBC [ 6 ], stage-specific comparisons were not performed in this meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…L YMPHOVASCULAR INVASION (LVI), defined as the infiltration of tumor cells into lymphatic or blood vessels at the periphery of the invasive carcinoma, 1 has been widely recognized as a negative prognostic factor in invasive breast cancer. [2][3][4][5][6] Studies have revealed that LVI status facilitates the selection of an optimal therapeutic strategy for individual breast cancer patients. [7][8][9][10][11] The extent of LVI is an important factor for predicting neoadjuvant chemotherapy (NAC) efficacy.…”
mentioning
confidence: 99%